Fazlur Rahman's Thoughts of Double Movement in the Context of the Development of Unity of Sciences - Janah, Nasitotul; Nugroho, Irham (Jurnal Tarbiyatuna, 2022)
The paradigms of rationalism, empiricism and positivism as the basis for the development of Western science adopted by the Islamic world have led to the emergence of a dichotomy and dualism that puts science and religion a vis a. The implication is that science becomes value-less, wild, secular and sometimes destructive. Science and religion are two independent entities, do not interfere with each other and are in different zones, even their relationship is sometimes colored by conflict that negates each other. To find a solution to this situation, ideas and concepts for the integration of science and religion, such as de-westernization and Islamization of knowledge, emerged from Islamic thinkers as an effort to build a more harmonious, conducive, and constructive relationship between science and religion. However, this idea received resistance from Fazlurrahman because according to him science is objective so that Islamization or dewesternization is not needed, but rather integration or unity of science. This research is a library research. Sources of data were obtained through various written works, both in the form of books and journals, to find out how relevant Fazlurrahman's thoughts are in the context of developing unity of science in the Islamic world. The results of this study offer the concept of returning knowledge to its natural state by placing Allah as the main source of knowledge in the context of the ontological dimension; making the universe (kauniyyah verse) and sacred texts of the holy book (qauliyyah verse) a source of knowledge in the context of the epistemological dimension; in its application and implementation, science must have a moral responsibility to humanistic values ​​in the context of the axiological dimension.